Analisis Komparatif Kecerdasan Emosional dan Pemahaman Akuntansi Biaya Berdasarkan Gender pada Mahasiswa Manajemen Bisnis Internasional Politeknik Negeri Bali - Galang Marhaenis Luh; Elsa Karina Maria; Dananjaya Gede Ida Bagus (JURNAL MANAJEMEN DAN BISNIS EKONOMI, 2026)
This study aims to analyze the differences in emotional intelligence and students' understanding of Cost Accounting courses viewed from a gender perspective. The complexity of Cost Accounting material requires not only cognitive abilities but also emotional stability in problem-solving. The research method used is quantitative comparative with a sample of International Business Management (IBM) students at Bali State Polytechnic. Data were collected through emotional intelligence questionnaires and material understanding tests, which were then processed using t-test analysis via Microsoft Excel. The results showed that [there is/there is no] significant difference between male and female students in understanding Cost Accounting. Furthermore, it was found that emotional intelligence plays a crucial role in helping students manage pressure when preparing cost reports. The implication of this research is the need for adaptive teaching approaches for IBM lecturers to balance technical competence and psychological aspects regardless of gender differences. Furthermore, these results are also expected to be the basis for developing more effective and inclusive learning methods in higher education environments.